Non-Clinical Safety Evaluation of Intranasal Iota-Carrageenan - Hebar, Alexandra; Koller, Christiane; Seifert, Jan-Marcus; Chabicovsky, Monika; Bodenteich, Angelika; Bernkop-Schnürch, Andreas; Grassauer, Andreas; Prieschl-Grassauer, Eva (PLOS ONE, 2015)
Carrageenan has been widely used as food additive for decades and therefore, an extended oral data set is available in the public domain. Less data are available for other routes of administration, especially intranasal administration. The current publication describes the non-clinical safety and toxicity of native (non-degraded) iota-carrageenan when applied intranasally or via inhalation. Intranasally applied iota-carrageenan is a topically applied, locally acting compound with no need of systemic bioavailability for the drug’s action. Animal experiments included repeated dose local tolerance and toxicity studies with intranasally applied 0.12% iota-carrageenan for 7 or 28 days in New Zealand White rabbits and nebulized 0.12% iota-carrageenan administered to F344 rats for 7 days. Permeation studies revealed no penetration of iota-carrageenan across nasal mucosa, demonstrating that iota-carrageenan does not reach the blood stream. Consistent with this, no relevant toxic or secondary pharmacological effects due to systemic exposure were observed in the rabbit or rat repeated dose toxicity studies. Data do not provide any evidence for local intolerance or toxicity, when carrageenan is applied intranasally or by inhalation. No signs for immunogenicity or immunotoxicity have been observed in the in vivo studies. This is substantiated by in vitro assays showing no stimulation of a panel of pro-inflammatory cytokines by iota-carrageenan. In conclusion, 0.12% iota-carrageenan is safe for clinical use via intranasal application.